The Anti-Adiposity Mechanisms of Ampelopsin and Vine Tea Extract in High Fat Diet and Alcohol-Induced Fatty Liver Mouse Models - Wu, Jianbo; Miyasaka, Kenchi; Yamada, Wakana; Takeda, Shogo; Shimizu, Norihito; Shimoda, Hiroshi (Molecules (Basel, Switzerland), 2022)
Ampelopsis grossedentata (AG) is an ancient medicinal plant that is mainly distributed and used in southwest China. It exerts therapeutic effects, such as antioxidant, anti-diabetic, and anti-inflammatory activities, reductions in blood pressure and cholesterol and hepatoprotective effects. Researchers in China recently reported the anti-obesity effects of AG extract in diet-induced obese mice and rats. To verify these findings, we herein investigated the effects of AG extract and its principal compound, ampelopsin, in high-fat diet (HFD)- and alcohol diet-fed mice, olive oil-loaded mice, and differentiated 3T3-L1 cells. The results obtained showed that AG extract and ampelopsin significantly suppressed increases in the weights of body, livers and abdominal fat and also up-regulated the expression of carnitine palmitoyltransferase 1A in HFD-fed mice. In olive oil-loaded mice, AG extract and ampelopsin significantly attenuated increases in serum triglyceride (TG) levels. In differentiated 3T3-L1 cells, AG extract and ampelopsin promoted TG decomposition, which appeared to be attributed to the expression of hormone-sensitive lipase. In alcohol diet-fed mice, AG extract and ampelopsin reduced serum levels of ethanol, glutamic oxaloacetic transaminase (GOT), and glutamic pyruvic transaminase (GPT) and liver TG. An examination of metabolic enzyme expression patterns revealed that AG extract and ampelopsin mainly enhanced the expression of aldehyde dehydrogenase and suppressed that of cytochrome P450, family 2, subfamily e1. In conclusion, AG extract and ampelopsin suppressed diet-induced intestinal fat accumulation and reduced the risk of fatty liver associated with HFD and alcohol consumption.